Knowledge and Attitude of Pregnant Women Undergoing Cell-free DNA Screening at the King Chulalongkorn Memorial Hospital - Patcharaporn Chalopagorn; Saknan Manotaya (The Royal Thai College of Obstetricians and Gynaecologists, 2019)
Objectives: To investigate the knowledge and attitude of pregnant women before undergoing cell-free DNA screening at King Chulalongkorn Memorial Hospital (KCMH). Materials and Methods: A cross-sectional study recruited 400 singleton pregnant women who underwent cell-free DNA screening at KCMH from December 2016 to August 2017. Self-administered questionnaires were used to evaluate participants' knowledge and attitude. Results: Four-hundred pregnant women answered the questionnaires and 344 responses were considered valid. The maternal age ranged from 23 to 46 years and mean age was 34.8 ± 3.6 years. Almost all of the participants answered correctly about the test's ability to detect trisomy 21, trisomy 18, trisomy 13, and fetal sex (96.8, 83.7, 84.8, and 93.9% respectively). Eighty-nine percent of the women answered correctly about the time to start cell-free DNA testing, and 68% answered correctly about detection rate of trisomy 21. Some participants had misconceptions about the test's ability such as false negative rate, thalassemia screening, fetal malignancy detection, autistic detection, cleft lip-cleft palate detection, and the option of termination of pregnancy if the screening was positive. Seventy-nine percent were aware of the possibility of re-sampling. Additional data showed that participants had positive attitude towards cell-free DNA screening, and preferred to use it again for future pregnancy. Conclusion: Our study showed that the majority of the participants had good knowledge of the test's ability to detect trisomy, and a possibility of re-sampling. However, almost half of the participants misunderstood that it could detect all genetic abnormalities. This study showed the magnitude of expectations and misunderstandings about cell-free DNA screening.